Budaya Organisasi, Pelatihan, Motivasi dan Kepuasan terhadap Kinerja Perawat di Rs Ibu dan Anak (Rsia) ‘Aisyiyah Klaten - Moh Ma'ruf; Sudarwati; Istiatin (SAFE-Network, 2023)
The purpose of this study was to find out how organizational culture, training, motivation, and job satisfaction influence nurse performance. This research method is quantitative descriptive correlational. The sample used was 80 nurses, data collection using a questionnaire was carried out in May-June 2023. The results showed that organizational culture, training, motivation, and satisfaction with performance obtained r= 0.622, 0.579, 0.615, 0.609 with the probability of each of these variables being 0.000 <0.005, which means that there is a significant relationship/correlation between organizational culture, training, motivation, and satisfaction with performance. In addition, each of these variables describes a positive relationship, which means that the higher the organizational culture, the training, increased motivation and the higher the level of satisfaction, the higher the performance of nurses. The conclusion from this study is that organizational culture, training, motivation, and satisfaction affect the performance of nurses at RSIA ‘Aisyiyah Klaten.